Effects of dose calculation algorithms on the estimate NTCP for thoracic cancer. (March 2020) - Rahman, W N; R Ab, Rashid; Abdullah, R
Abstract: The study aims to investigate the effect of dose calculation algorithms on the estimate normal tissue complication probability (NTCP) of thoracic cancer. Dose distributions of treatment plans are calculated by using Collapsed Cone (CC) and Pencil Beam (PB) algorithms from Oncentra Masterplan treatment planning system. Four treatment plans of thoracic cancers are created and dose volume histograms (DVHs) from each planning were evaluated based on criteria of acceptance level. The DVH data of the treatment planning were exported to Biosuite Software to compute the NTCP values. The NTCP were calculated accounting for the CC and PB algorithm using the Lyman-Kutcher-Burman (LKB) and Relative Seriality (RS) model. The NTCP values of the LKB model are found to have slightly higher values compare to RS model for all treatment planning using both algorithms. This study also demonstrates that the dose calculation algorithms of CC and PB did not significantly influence the computed NTCP value in the present treatment planning of thoracic cancer.